The Effect of Using Blended Learning Strategy toward the 8 Grade Students’ Writing Competency - Yoga Gede Permana (Journal of Psychology and Instruction, 2017)
This study was aimed at investigating whether or not there was significant difference in writing competency between students who were taught by using blended learningand those who were taught by using conventional strategy. The research design used in this study was Post-test Only Control Group Design. The population in this study was eight grade students of SMP Negeri1Singaraja andthe samples of study were selected by using Cluster Random Sampling. Class VIII A8was assigned as the experimental group which was taught by using “blended learning” and class VIII A7 as the control group which was taught by using “conventional strategy”. The result of the data analysis showed that students in the experimental group performed better than the students in the control group. It was proven by the result of the descriptive statistics that showed the mean scoreof the experimental group was 84.75while the mean score of the control group was 76.75. The result of the t-test also showed that the value of the tob was higher than the tcv. The value of the tob was-6.379, while the value of the tcv was1.6736(α = 0.5). It means that there was a significant difference on writing competency between the students who were taught by using blended learningstrategy and those who were taught by using conventional strategy.